A Comparative Study of Vocabulary Learning Strategies Used by Marine Engineering Students and Iranian EFL Learners - Davood Mashhadi Heidar; Majid Sadeghzadeh Hemayati (Research in English Language Pedagogy, 2017)
The present study explored the vocabulary learning strategies used by Iranian EFL learners and Marine Engineering (ME) students by using the categorization of vocabulary learning strategies proposed by Schmitt (1997). A vocabulary learning strategies questionnaire was administered to 30 EFL learners and 43 ME students. Then, the strategies used by each group were determined and the two groups were compared with each other. It was found that both groups used determination strategies more frequently than social strategies for discovering a new word’s meaning. The most frequently used discovery strategy by both groups was found to be “bilingual dictionary”. The second and third most frequently used strategy for discovery by EFL learners and ME students was found to be “monolingual dictionary” and “guess from textual context”, respectively. It was also revealed that EFL learners used memory strategies more frequently than other strategies for consolidating the meaning of new words and ME students used cognitive strategies the most frequently. Both groups were found to use “verbal repetition” more frequently than all other consolidation strategies. The second most frequently used strategy by EFL learners was “use Englishlanguage media” whilst for ME students they were “written repetition” and “word lists”. The comparison of the strategy use by the participants in the two groups showed no significant difference.